2011
DOI: 10.5607/en.2011.20.4.159
|View full text |Cite
|
Sign up to set email alerts
|

The Serotonin-6 Receptor as a Novel Therapeutic Target

Abstract: Serotonin (5-hydroxytryptamine, 5-HT) is an important neurotransmitter that is found in both the central and peripheral nervous systems. 5-HT mediates its diverse physiological responses through 7 different 5-HT receptor families: 5-HT1, 5-HT2, 5-HT3, 5-HT4, 5-HT5, 5-HT6, and 5-HT7 receptors. Among them, the 5-HT6 receptor (5-HT6R) is the most recently cloned serotonin receptor and plays important roles in the central nervous system (CNS) and in the etiology of neurological diseases. Compared to other 5-HT rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 67 publications
0
53
1
3
Order By: Relevance
“…It was previously reported that 5-HT 6 R physically and functionally interacts with Jab1 and the activation of 5-HT 6 R releases Jab11324. Jab1 has been reported to interact with Smad5 and cause an attenuation of BMP-dependent transcriptional responses, suggesting that Jab1 might act as an inhibitor of BMP signaling26.…”
Section: Resultsmentioning
confidence: 98%
“…It was previously reported that 5-HT 6 R physically and functionally interacts with Jab1 and the activation of 5-HT 6 R releases Jab11324. Jab1 has been reported to interact with Smad5 and cause an attenuation of BMP-dependent transcriptional responses, suggesting that Jab1 might act as an inhibitor of BMP signaling26.…”
Section: Resultsmentioning
confidence: 98%
“…Based on previous studies, a more likely explanation for antidepressant-like effects of 5-HT 6 receptor agonist and antagonist is that the analogous behavioral effects are mediated through different neurochemical mechanisms. 5-HT 6 receptor agonists produce antidepressant-like effects similar to those of selective serotonin reuptake inhibitors (SSRIs) through global stimulation of postsynaptic 5-HT receptors, and the effects may also involve in improvement of GABA neurotransmission, whereas the effects of 5-HT 6 receptor antagonists involve in enhancement of brain DA and NA neurotransmission (Wesolowska, 2010;Yun and Rhim, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been documented that increased Fyn expressions would possibly induce activation of ERK1/2 to phosphorylated ERK1/2 (p-ERK1/2) through interacting with the carboxyl-terminal region of HTR6 [31,32]. ERK1/2 that was highly expressed in the central nervous system could affect the formation of MFS by modulating neurotransmitters, neurotropic factors (e.g.…”
Section: Discussionmentioning
confidence: 99%